Pelaksanaan Pengelolaan Sampah Domestik Oleh BUM Desa - Sulistiyani, Lilik; Dahlia, Nelly (IDFoS Indonesia, 2022)
As part of efforts towards Indonesia's Free of Waste, Bojonegoro Regency implemented the Garbage Emergency program in 2020. This program includes strategies for waste utilization and determining the location of Final Waste Disposal Sites. Through collaboration between the Village Government and Village-Owned Enterprises (BUMDesa), innovations have been created to address household waste issues. The domestic waste management program managed by BUMDesa targets the direct participation of households in waste sorting and storage according to its classification, with the hope of reducing the accumulation of waste that pollutes the environment. This research aimed to analyze the implementation of domestic waste management by Village-Owned Enterprises. The method used in this research employed a qualitative approach with a case study design. The research focused on six indicators: policy standards and objectives, resources, characteristics of implementing agents, inter-organizational communication, socio-economic-political conditions, and the disposition of implementers, with data collection techniques including interviews, literature review, and documentation. Findings from this research indicated that the implementation of waste management programs in Sambiroto Village involves cooperation between the village government, Village-Owned Enterprises, and residents. This program aimed to reduce the volume of waste originating from households by actively involving community participation. However, the implementation of this program faces challenges, including limited resources and a lack of financial support from the community. The village government needed to improve communication and provide training for the community and personnel involved in the program. Additionally, providing subsidies or assistance to low-income communities can also enhance participation in waste management. With the hope that this program can have a positive impact on environmental cleanliness and increase public awareness of the importance of sustainable waste management.